PENGARUH KEHALUSAN FLY ASH TERHADAP SUBTITUSI SEMEN PCC PADA BETON SCC (SELF COMPACTING CONCRETE) - Ramandani, M. Rizky; Firdaus, Firdaus (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
This study aims to analyze the effect of the fineness and percentage of fly ash as a partial substitute for cement on the mechanical properties of Self Compacting Concrete (SCC). Fly ash from PT. Pupuk Sriwidjaja was classified into three fineness zones (Zone 1, 2, and 3) and used as a cement substitute at varying percentages of 5%, 10%, and 15%. The research method employed was an experimental laboratory study involving tests for compressive strength (7, 14, 28 days), split tensile strength (28 days), and modulus of elasticity (28 days). The results indicated that the addition of fly ash improved the workability of fresh concrete, as shown by the slump flow values that met the EFNARC specifications. At 28 days, the compressive strength of the concrete increased with the higher percentage and fineness of fly ash, with the highest value of 44.18 MPa achieved in the mix with 15% Zone 3 fly ash, surpassing the normal concrete (40.05 MPa). Conversely, the split tensile strength of the concrete decreased significantly across all fly ash variations. The modulus of elasticity increased with fly ash usage up to 10%, reaching a peak value of 31,176.27 MPa, but decreased at the 15% substitution level. In conclusion, the fineness and percentage of fly ash significantly influence the mechanical properties of SCC. Fly ash with higher fineness (Zone 3) and at specific percentages (10-15%) can enhance compressive strength and modulus of elasticity, although it reduces split tensile strength. The use of 10% Zone 3 fly ash provides the optimal results for improving the stiffness and compressive strength of SCC.Keywords: Self Compacting Concrete (SCC), Fly Ash, Fineness, Compressive Strength, Split Tensile Strength, Modulus of Elasticity